2020
DOI: 10.3390/nu12113311
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Effect of a Novel Simply Calculated Nutritional Index in Acute Decompensated Heart Failure

Abstract: The TCB index (triglycerides × total cholesterol × body weight), a novel simply calculated nutritional index based on serum triglycerides (TGs), serum total cholesterol (TC), and body weight (BW), was recently reported to be a useful prognostic indicator in patients with coronary artery disease. Thus, this study aimed to investigate the relationship between TCBI and long-term mortality in acute decompensated heart failure (ADHF) patients. Patients with a diagnosis of ADHF who were consecutively admitted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…The TCBI index, a novel nutritional metabolism index, is calculated from variables reflecting lipid metabolism measured from blood tests. Some studies showed that TCBI was a useful prognostic indicator in patients with a wide range of CVD ( 11 , 40 , 41 ). The most significant advantage of the TCBI is the simplicity of the calculation, which saves time and effort in caring for and treating ICU (intensive care unit) patients ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TCBI index, a novel nutritional metabolism index, is calculated from variables reflecting lipid metabolism measured from blood tests. Some studies showed that TCBI was a useful prognostic indicator in patients with a wide range of CVD ( 11 , 40 , 41 ). The most significant advantage of the TCBI is the simplicity of the calculation, which saves time and effort in caring for and treating ICU (intensive care unit) patients ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that TCBI was a useful prognostic indicator in patients with a wide range of CVD ( 11 , 40 , 41 ). The most significant advantage of the TCBI is the simplicity of the calculation, which saves time and effort in caring for and treating ICU (intensive care unit) patients ( 40 , 41 ). The calculation of TCBI simply requires multiplying three variables, while anyone who calculates GNRI or PNI needs to know the constant values and how to calculate ideal body weight.…”
Section: Discussionmentioning
confidence: 99%
“…In hospitalized critical patients with mechanical circulatory support devices, TCBI was an independent predictor of all-cause mortality ( Minami-Takano et al, 2019 ). In patients with acute decompensated heart failure, TCBI can improve the prognostic prediction over traditional risk factors such as hemoglobin and serum sodium level ( Ishiwata et al, 2020 ). Similarly, our study contributes to the existing literature on the relation of TCBI with DCM outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Some simplified nutritional screening tools such as the Geriatric Nutritional Risk Index (GNRI), the prognostic nutritional index (PNI), and the Controlling Nutritional Status (CONUT), have been found to predict the outcome of heart failure ( Lin et al, 2016 ). Recently, a novel nutritional index, triglycerides × total cholesterol × body weight index (TCBI), has been proposed to be a useful prognostic indicator in patients with CAD ( Doi et al, 2018 ; Kim et al, 2021 ), acute decompensated heart failure ( Ishiwata et al, 2020 ), and critically ill patients ( Minami-Takano et al, 2019 ). However, in patients with DCM, the prognostic value of TCBI has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…A novel and more precise scoring system has been recently proposed: The Geriatric Nutritional Risk Index (GNRI) [ 9 ]. It has been validated in institutionalized patients [ 10 ], dialysis patients [ 11 ], and patients with heart failure [ 12 ]. GNRI scoring includes serum albumin; therefore, it may be better correlated with systemic inflammation in the elderly.…”
Section: Introductionmentioning
confidence: 99%